2022
DOI: 10.3390/foods11081093
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance and Molecular Characterization of Cronobacter sakazakii Strains Isolated from Powdered Infant Formula Milk

Abstract: Background: Cronobacter sakazakii is a new emerging foodborne bacterial pathogen associated with severe lethal diseases such as meningitis, necrotizing enterocolitis, and septicemia in infants and neonates. Powdered infant formula milk (PIFM) has been recognized as one of the main transmission vehicles and contaminated sources of this pathogen. This study aimed to investigate the prevalence rate, genotypic and phenotypic antibiotic resistance profile, and clonal relatedness of C. sakazakii strains isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…This study revealed the presence of Cronobacter sp in the analyzed urine samples. Cronobacter sp had been reported as emerging pathogens from infant food [41] . The incidence of UTI cause by Cronobacter sp in the study area is rear.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed the presence of Cronobacter sp in the analyzed urine samples. Cronobacter sp had been reported as emerging pathogens from infant food [41] . The incidence of UTI cause by Cronobacter sp in the study area is rear.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleic acid detection methods for pathogenic Y. enterocolitica are mainly based on PCR, multiplex PCR, qPCR, and RPA [ 14 , 15 , 16 ]. Although PCR is widely used for foodborne pathogenic bacteria [ 17 ], the associated complex (high-cost) instrumentation and laboratory requirements for visualization of the results (gel electrophoresis) with traditional PCR can prohibit its use in underdeveloped countries/regions with limited resources, and in onsite diagnostics [ 18 ]. Compared with PCR, the amplification process of qPCR is presented in real time [ 19 ], and it can provide more robust, specific, and sensitive quantitative results.…”
Section: Introductionmentioning
confidence: 99%
“…15 Although clinical cases are rare, they can be severe, and cases of meningitis and septicemia do occur at both extremes of the age range. 15…”
mentioning
confidence: 99%
“…14 A review from Switzerland found that Cronobacter contamination is widespread with a prevalence of 3% to 30% in powdered milk products. 15 Although clinical cases are rare, they can be severe, and cases of meningitis and septicemia do occur at both extremes of the age range. 15 Other contaminants have also been found in infant formula from time to time.…”
mentioning
confidence: 99%
See 1 more Smart Citation